Change in the dielectric properties of normal and relaxor ferroelectric ceramic composites in BT-PZT and PMN-PZT systems by an uniaxial compressive stress - Rattikorn Yimnirun (2018)
Effects of an uniaxial compressive pre-stress on the dielectric properties of normal and relaxor ferroelectric ceramic composites in BT-PZT and PMN-PZT systems are investigated. The dielectric properties are observed under the compressive pre-stress levels up to 15 and 5 MPa for BT-PZT and PMN-PZT, respectively, using a uniaxial compressometer. Both the dielectric constant and the dielectric loss tangent of the BT-PZT ceramics increase significantly with increasing applied stress. Larger changes in the dielectric properties with the applied stress are observed in the PZT-rich compositions. For PMN-PZT ceramics, the dielectric constant of the PZT-rich compositions increases slightly, while that of the PMN-rich compositions decreases with increasing applied stress. On the other hand, changes in the dielectric loss tangent with stress are found to be compositional independent. The experimental results are explained with the domain wall motion and de-aging mechanisms from the application of the compressive pre-stress. More importantly, this study undoubtedly shows that the applied stress significantly influences the dielectric properties of both ceramic composite systems.